CATEGORIZATION OF ISLAMIC THINKING (BAYANI AND BURHANI) - Dalmi Iskandar Sultani Iskandar Sultani; Mukhlis Mukhlis; Syarifuddin Syarifuddin; Ano Suherlan; Hasan Bakti Nasution (Sensei International Journal of Education and Linguistic, 2022)
Categorization of Islamic thinking (bayani and burhani). Using library research, with literature data sources, books, articles, manuscripts. Shows that epistemology talks about the sources and ways of obtaining knowledge. Sources of knowledge include; mind, senses, heart, and religion. How to gain knowledge by functioning of the senses of the heart, religion that is adapted to the character of religion. As a categorization of thinking, Bayani means continuity, separate or separate, clear, bright, the ability to make light and clear. Characterized by textual reasoning used to analyze the texts of the texts (al-Qur'an and hadith). Burhani means argument, which is clear. Centered on the power of the senses, reason with the rules of logic. Used by philosophers to study, understand objects in the non-physical realm.